PENINGKATAN PRESTASI BELAJAR IPS SISWA MELALUI METODE STUDENT TIMES ACHIEVMENT DIVISION (STAD) - Sutrisno Sutrisno (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2019)
Â AbstractThis study aims to improve social studies learning achievements through the Student Times Achievement Division (STAD) method in third grade students of Ngraho State Elementary School Kedungtuban Blora. The subject of this study was 15 students, consisting of 8 male students and 7 female students. This study is a Classroom Action Research model Kemnis and Mc. Taggart. This research was conducted in 2 cycles, each cycle consisting of 2 meetings. In each cycle there are 4 stages, namely planning, action, observation and reflection. The research instrument used was the test item, observation sheet and student response questionnaire. The test results data were analyzed quantitatively descriptively using the average learning achievement and the percentage of mastery learning. Data from observations and student responses were analyzed by calculating percentages. In the pre-cycle students who completed KKM were 5 students (33.33%). After the action of the first cycle increased to 11 students (73.12%), while in the second cycle increased to 13 students (86.66%). From cycle I to cycle II it increased 13.33%. The KKM completeness increased because students' social studies learning achievements improved from pre-cycle to cycle I and cycle I to cycle II. The average student learning achievement and the number of students who reach KKM have met the indicators of success, thus this study was stopped in cycle II.Keywords: Social Studies Learning Achievement, Student Times Achievment Division (STAD) Method.